Conceptualisation of evil in African Christian theology - C. Wethmar (Acta Theologica)
The aim of this article is to give an account of the interaction between Christianity and African Traditional Religion found in African Christian theology. The comparison is made with special reference to the respective conceptualisations of evil present in each of these traditions. The paper commences with a brief survey of the manner in which the notion of evil features in the Christian Scriptures and tradition. A brief outline of the African world and life view is then presented in order to provide the back-drop against which an analysis of the notion of evil in African Traditional Religion can be attempted. This analysis is mainly made with reference to recent research on witchcraft and spirit beliefs and is followed by a portrayal of the interaction between the traditional Christian views on evil and those found in African Traditional Religion. This interaction exhibits the twofold structure of rejection on the one hand and accommodation on the other.